Hydrocarbon polymer surface carbon film and preparation method thereof

The amorphous carbon film is constructed on the surface of hydrocarbon polymers by plasma immersion ion implantation, which solves the problems of uneven coating thickness and insufficient binding force in the existing carbon film preparation technology, and achieves efficient carbonization and absorbance on the material surface promote.

CN119505328APending Publication Date: 2025-02-25SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311078887.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing carbon film preparation technology has problems such as uneven coating thickness, insufficient bonding force, high cost and poor material surface quality stability.

Method used

A plasma immersion ion implantation method is used to construct an amorphous carbon film with a large conjugated structure on the surface of hydrocarbon polymers, and a graphite-like structure is formed through bombardment of high-energy particles and positive ion addition, thereby improving the graphitization degree and light absorption degree of the material surface.

Benefits of technology

The uniformity and bonding requirements of the amorphous carbon film are achieved, the carbonization and absorbance of the material surface are improved, the process is simple and the conditions are easy to control, and the coating is removed and other problems are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505328A_ABST
    Figure CN119505328A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrocarbon polymer surface carbon film and a preparation method thereof. The hydrocarbon polymer surface carbon film comprises a hydrocarbon polymer material serving as a matrix and an amorphous carbon film which is generated in situ and has a large conjugated structure, preferably, the hydrocarbon polymer material comprises at least one of polyethylene, polypropylene and polystyrene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for rapid carbonization of hydrocarbon polymer surfaces, that is, constructing a layer of amorphous carbon film on the material surface by plasma injection, and belongs to the field of surface treatment of hydrocarbon polymer materials. Background Art

[0002] There are many methods for surface modification of hydrocarbon polymers, such as chemical vapor deposition, atomic layer deposition and other chemical methods and physical methods such as magnetron sputtering. Various methods can be used to modify the surface of hydrocarbon polymers to make the material meet the requirements of use.

[0003] Carbon film has attracted wide attention from the industry due to its high electrical conductivity, high thermal conductivity, high lubricity and other properties. Currently, the following technologies are used to prepare carbon film on hydrocarbon polymer surface: evaporation, laser ablation, DLC (Diamond Like Carbon) film deposition, etc. These methods have their own shortcomings. The thickness of the coating obtained by evaporation is uneven, and the bonding force between the film and the substrate is not strong; laser ablation is costly, consumes a lot of gas, and the surface quality stability of the material is not very good; DLC film has the disadvantage of large internal stress in the coating. Summary of the invention

[0004] In order to solve the shortcomings of existing carbon film preparation methods, the present invention provides a carbon film on the surface of a hydrocarbon polymer material and a preparation method thereof, which can not only meet the requirements of film uniformity and bonding strength, but also has higher efficiency.

[0005] In one aspect, the present invention provides an oxygen-containing polymer surface carbon film, comprising a hydrocarbon polymer material as a matrix, and an in-situ generated amorphous carbon film having a large conjugated structure; Preferably, the hydrocarbon polymer material includes at least one of polyethylene, polypropylene and polystyrene.

[0006] Preferably, the carbon film on the surface of the hydrocarbon polymer has an absorbance in the visible light region of 0.1 to 0.5.

[0007] Preferably, the amorphous carbon film with a large conjugated structure has a Raman wavelength of 1580 cm -1 The intensity of the G peak is 4000-10.

[0008] On the other hand, the present invention provides a method for preparing a carbon film on the surface of a hydrocarbon polymer, wherein an amorphous carbon film having a large conjugated structure is prepared on the surface of a hydrocarbon polymer material by plasma immersion ion implantation.

[0009] The present invention mainly adopts ion implantation to form a layer of amorphous carbon film coating in situ on the surface of hydrocarbon polymer, which can improve the graphitization degree and light absorption degree of the material surface and has great potential in future applications.

[0010] The present invention proposes a simple method for constructing a layer of amorphous carbon film on the surface of hydrocarbon polymers by ion implantation. Plasma immersion ion implantation (PIII) is a surface modification technology that uses high-voltage pulsed direct current to inject accelerated ions in plasma as dopants into a suitable substrate or a target of a semiconductor chip with electrodes. It has the advantages of high efficiency and good adhesion between the coating and the substrate. When plasma immersion implantation is performed on the surface of hydrocarbon polymers, high-energy particles bombard the material, causing molecular chain breakage, cross-linking, dehydrogenation, deoxidation and carbonization on the surface of the material, ultimately resulting in the formation of a graphite-like carbonized modified layer on the surface of the material.

[0011] Preferably, the plasma used in the plasma immersion ion implantation is hydrogen plasma, argon plasma, oxygen plasma and nitrogen plasma. In the present invention, different plasmas are injected to produce carbon films with different graphitization degrees. The principle is that the different nucleophilic abilities of positive ions to activate carbon chains will affect the formation of graphite-like structures.

[0012] In the present invention, the mechanism of using hydrogen plasma to inject an amorphous carbon film on the surface of a hydrocarbon polymer is as follows: on the one hand, the bombardment of high-energy particles will cause unsaturated carbon to form on the surface of the material, and the unsaturated carbons can cross-link with each other to form a graphite-like structure on the surface of the material; on the other hand, hydrogen cations have electrophilic properties and can add to unsaturated bonds to generate carbon cations, and then the electrophilicity of carbon cations will allow them to react with other electron-rich groups. Hydrogen can only have one covalent bond, so the carbon cations in the hydrogen injection process can only react with other unsaturated carbons, thereby achieving the interconnection of the ring structure and the enhancement of the degree of graphitization. At the same time, the weak electrophilicity of hydrogen cations allows it to dissociate from the carbon chain relatively easily, thereby not destroying the original conjugated system.

[0013] In the present invention, the mechanism of using argon plasma to inject an amorphous carbon film on the surface of a hydrocarbon polymer is that the bombardment of high-energy particles will cause unsaturated carbon to form on the surface of the material, and the cross-linking between the unsaturated carbons can form a graphite-like structure on the surface of the material. Among them, the carbonization mechanism of the hydrocarbon polymer is the activation of the carbon chain by the nucleophilicity of the positive ions.

[0014] In the present invention, the mechanism of injecting oxygen plasma into the surface of hydrocarbon polymer to produce amorphous carbon film is: the bombardment of high-energy particles will cause unsaturated carbon to form on the surface of the material, and the cross-linking between unsaturated carbon can form a graphite-like structure on the surface of the material, but oxygen plasma is easy to add to the surface of the material, destroying the conjugated structure on the surface of the material, so the degree of graphitization of the surface of the material is low. Among them, the carbonization mechanism of hydrocarbon polymers is the activation of carbon chains by the nucleophilicity of positive ions.

[0015] Preferably, the parameters of the plasma immersion ion implantation include: the background vacuum of the ion implantation equipment is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×100Pa, the ion source power is 50~1200W, the negative voltage is 10kV~50kV, and the duty cycle is 10%~80%; the introduced gas is hydrogen, argon, oxygen or nitrogen.

[0016] Beneficial effects of the present invention: 1) The amorphous carbon film produced by the method provided by the present invention has excellent bonding strength with the substrate material, and there will be no phenomenon of coating shedding; 2) The method for preparing the carbon film on the surface of hydrocarbon polymer provided by the present invention has simple process and easily controllable conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the light absorption result of the polymer surface carbon film prepared in Example 1. It can be seen from the figure that the overall light absorption intensity of the sample treated in Example 1 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest; Figure 2 This is the infrared result of the polymer surface carbon film prepared in Example 1. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 1 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material Figure 3 This is the light absorption result of the polymer surface carbon film prepared in Example 2. It can be seen from the figure that the overall light absorption intensity of the sample treated in Example 2 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest; Figure 4 This is the infrared result of the high molecular oxygen-containing carbon film prepared in Example 2. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 2 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material. Figure 5This is the Raman result of the sample prepared in Example 2. It can be seen from the figure that the sample treated in Example 2 has the G peak and D peak unique to graphite on its surface, indicating that a certain graphite-like structure has been produced on the surface. The ratio of the Raman D peak intensity to the G peak intensity represents the degree of surface graphitization. It can be seen from the figure that hydrogen plasma injection carbonization has the best effect. However, hydrogen plasma injection cannot significantly increase the total surface SP2 carbon content, which verifies our speculation. Figure 6 This is the light absorption result of the polymer surface carbon film prepared in Example 3. It can be seen from the figure that the overall light absorption intensity of the samples treated in Example 2 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest; Figure 7 This is the infrared result of the polymer surface carbon film prepared in Example 3. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 2 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material. Figure 8 This is the Raman result of the sample prepared in Example 3. It can be seen from the figure that the sample treated in Example 2 has a D peak unique to graphite on its surface, indicating that the surface has undergone a certain degree of graphitization. However, the absorption peak at 1350 of the unmodified sample overlaps with the D peak to a certain extent, so it is impossible to determine the degree of surface graphitization by Raman. Fig. 9 The infrared result graphs of the carbon films on the surfaces of non-hydrocarbon polymers prepared in Examples 4, 5 and 6 show that the overall infrared absorption intensity of the samples treated in Examples 4, 5 and 6 is reduced, indicating that the ion implantation process has caused damage to the surface structure of the material. Fig.10 The light absorption results of the carbon film on the surface of the non-hydrocarbon polymer prepared in Examples 4, 5, and 6 are shown in the figure. It can be seen from the figure that the overall light absorption intensity of the samples treated in Examples 4, 5, and 6 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The absorption of the material after hydrogen plasma treatment is the strongest, indicating that its surface carbonization degree is the highest. DETAILED DESCRIPTION

[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0019] The invention provides a method for constructing an oxygen-containing amorphous carbon film coating on the surface of a hydrocarbon polymer by plasma injection. The coating is formed by plasma injection.

[0020] The following is an exemplary description of a method for preparing an oxygen-containing amorphous carbon film.

[0021] The hydrocarbon polymer material (sheet) is ultrasonically cleaned and dried, wherein the solvent used for ultrasonic cleaning is ethanol, preferably anhydrous ethanol.

[0022] Plasma implantation is used to construct an amorphous carbon film with a thickness of nanometers on the surface of the material.

[0023] In an optional embodiment, hydrogen plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.

[0024] In an optional embodiment, argon plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.

[0025] In an optional embodiment, oxygen plasma is used, wherein the parameters include: the background vacuum of the plasma equipment during the injection process is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, ion source power is 50-1200W, negative voltage is 0.1-50kV, and duty cycle is 10%-80%.

[0026] In the present invention, the absorbance of the carbon film on the surface of hydrocarbon polymer at 500nm obtained by ultraviolet visible spectrophotometer is 0.1-0.7 in the visible light region. The intensity of the Raman 1580cm-1G peak of the carbon film on the surface of hydrocarbon polymer obtained by Raman spectrometer is 1000-6000.

[0027] In the present invention, an infrared spectrometer is used to test the surface carbon of the obtained hydrocarbon polymer.

[0028] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0029] Example 1 Step 1: Pretreatment: polishing a polystyrene PS disc with a thickness of 1.5 mm and a diameter of 12 mm; Step 2: Prepare the coating, place the sample in the ion implantation sample tray, evacuate to, and then perform ion implantation. The gas types are hydrogen, oxygen, argon, and nitrogen. The samples obtained in the experiment are marked as H-PS, O-PS, and Ar-PS. The specific parameters are shown in Table 1.

[0030] Table 1 shows the plasma injection parameters.

[0031] Example 2 The difference between Example 2 and Example 1 is that the hydrocarbon polymer in this example is polyethylene, and the other parameters are the same as those in Example 1. The samples obtained in the experiment are marked as H-PE, O-PE, and Ar-PE.

[0032] Example 3 The difference between Example 3 and Example 1 is that the hydrocarbon polymer in this example is polypropylene, and the other parameters are the same as those in Example 1. The samples obtained in the experiment are marked as H-PP, O-PP, and Ar-PP.

[0033] Example 4 The difference between Example 4 and Example 1 is that different voltage parameters are used in this example, namely -10kv, -20kv and -30kv. For other parameters, see Table 2.

[0034] Table 2 shows the plasma injection parameters.

[0035] Example 5 The difference between Example 5 and Example 2 is that different voltage parameters are used in this example, namely -10kv, -20kv and -30kv. For other parameters, see Table 3.

[0036] Table 3 shows the plasma injection parameters.

[0037] Example 6 The difference between Example 6 and Example 3 is that different voltage parameters are used in this example, namely -10kv, -20kv and -30kv. For other parameters, see Table 4.

[0038] Table 4 shows the plasma injection parameters

[0039] Table 6 shows the composition and properties of the oxygen-containing amorphous carbon film with a large conjugated structure prepared by the present invention: Among them, "none" means that there is no relevant data. Due to the functional groups of polymers, some test items are meaningless to them (the test peak intensity will overlap with the peak of the polymer itself and interfere with the experimental structure), so it is marked as "unable to test".

[0040] Example 7 The unmodified sample and the sample obtained in Example 1 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Figure 1 2 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Example 1 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The light absorption capacity of the surface treated with hydrogen plasma is the best among all treatment groups.

[0041] Example 8 The unmodified sample and the sample obtained in Example 1 were subjected to infrared spectroscopy test. The test range of the samples was 500-1500cm -1 . Figure 2 This is the infrared result diagram of the above sample. It can be seen from the figure that the overall infrared absorption intensity of the sample treated in Example 1 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. The PS surface contains benzene rings, so the SP2 carbon peak intensity cannot characterize the carbonization situation.

[0042] Example 9 The unmodified sample and the sample obtained in Example 2 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Figure 32 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Example 2 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The light absorption capacity of the surface treated with hydrogen plasma is the best among all treatment groups.

[0043] Example 10 The unmodified sample and the sample obtained in Example 2 were subjected to infrared spectroscopy test. The test range of the samples was 500-1500 cm -1 . Figure 4 This is the infrared result diagram of the above samples. It can be seen from the figure that the overall infrared absorption intensity of the samples treated in Example 2 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. The surface SP2 carbon and C=O bond absorption peak intensity of the surface treated with hydrogen plasma is the largest, which indirectly shows that the carbonization effect of hydrogen plasma implantation is the best.

[0044] Embodiment 11 The unmodified sample and the sample obtained in the above Example 2 were subjected to Raman spectroscopy test. The laser used was 325 nm. Figure 5 This is the Raman result diagram of the above sample. It can be seen from the figure that the sample treated in Example 2 has the G peak and D peak unique to graphite on its surface, indicating that a certain graphite-like structure has been produced on the surface. The ratio of the Raman D peak intensity to the G peak intensity represents the degree of surface graphitization. It can be seen from the figure that hydrogen plasma injection carbonization has the best effect. However, hydrogen plasma injection cannot significantly increase the total surface SP2 carbon content, which verifies our speculation.

[0045] Example 12 The unmodified sample and the sample obtained in the above Example 3 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Figure 6 3 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Example 3 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. The light absorption capacity of the surface treated with hydrogen plasma is the best among all treatment groups.

[0046] Example 13 The unmodified sample and the sample obtained in Example 3 were subjected to infrared spectroscopy test. The test range of the samples was 500-1500 cm -1 . Figure 7This is the infrared result diagram of the above samples. It can be seen from the figure that the overall infrared absorption intensity of the samples treated in Example 3 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. The surface SP2 carbon and C=O bond absorption peak intensity of the surface treated with hydrogen plasma is the largest, which indirectly shows that the carbonization effect of hydrogen plasma implantation is the best.

[0047] Embodiment 14 The unmodified sample and the sample obtained in the above Example 3 were subjected to Raman spectroscopy test. The laser used was 325 nm. Figure 8 This is the Raman result of the above sample. It can be seen from the figure that the sample treated in Example 2 has a G peak unique to graphite on its surface, indicating that a certain degree of graphitization has occurred on the surface. However, the total content of SP2 carbon on its surface cannot be significantly increased after hydrogen plasma injection, which is consistent with the previous results.

[0048] Embodiment 15 The unmodified sample and the samples obtained in Examples 4, 5, and 6 were subjected to infrared spectroscopy testing. The test range of the samples was 500-1500 cm -1 . Fig. 9 This is the infrared result diagram of the above samples. It can be seen from the figure that the overall infrared absorption intensity of the samples treated by Examples 4, 5, and 6 has decreased to a certain extent, indicating that the ion implantation process has caused damage to the surface structure of the material. For different polymers, as the voltage increases, the intensity of the unsaturated carbon and C=O characteristic peaks on their surfaces increases, indicating that the voltage is positively correlated with the degree of carbonization.

[0049] Example 16 The unmodified sample and the samples obtained in the above Examples 4, 5 and 6 were subjected to UV-visible spectrum test. The sample test range was 250-850nm. Fig.10 2 is the light absorption result diagram of the above samples. It can be seen from the figure that the overall light absorption intensity of the samples treated with the samples obtained in Examples 4, 5, and 6 has increased, indicating that after ion implantation, the conjugated system on the surface of the material has been extended, indicating that carbonization has occurred on the surface of the sample after treatment. For different polymers, as the voltage increases, their surface light absorption capacity increases accordingly, verifying the results of Example 15.

Claims

1. A carbon film on the surface of a hydrocarbon polymer, characterized in that: include: Hydrocarbon polymer materials as matrix, and in-situ generated amorphous carbon films with large conjugated structures; Preferably, the hydrocarbon polymer material includes at least one of polyethylene, polypropylene and polystyrene.

2. The carbon film on the surface of hydrocarbon polymer according to claim 1, characterized in that: The Raman 1580 cm -1 The intensity at the G peak is 1000-25000.

3. The carbon film on the surface of hydrocarbon polymer according to claim 1 or 2, characterized in that: The absorbance of the carbon film on the surface of the hydrocarbon polymer in the visible light region is 0.1-0.

5.

4. A method for preparing a carbon film on the surface of a hydrocarbon polymer, characterized in that: An amorphous carbon film with a large conjugated structure is prepared on the surface of a hydrocarbon polymer material by plasma immersion ion implantation.

5. The preparation method according to claim 4, characterized in that: The plasma used in the plasma immersion ion implantation is hydrogen plasma, argon plasma or oxygen plasma.

6. The method for modifying the surface of a hydrocarbon polymer according to claim 4 or 5, characterized in that: The parameters of the plasma immersion ion implantation include: the background vacuum of the ion implantation equipment is 1×10 -4 ~1×10 -2 Pa, the gas flow rate is 1-100 sccm, and the working vacuum is 1×10 -2 ~5×10 2 Pa, the ion source power is 50-1200W, the negative voltage is 10-50kV, and the duty cycle is 10%-80%; the introduced gas is hydrogen, argon, oxygen or nitrogen.